Liebestragödie. Genealogien einer französischen Gattung des 17. Jahrhunderts - Schlieper, Hendrik

Vexierbilder als gegenhegemoniales Moment. Strategien postmigrantischen Erzählens bei Andrea Karimé - Kißling, Magdalena; Seidel, Nadine (Literatur der Postmigration: Grundzüge, Formen und Vertreter_innen)

"Die Geschichte als Dichterin". Analogien in kleinen historischen Porträts von Stefan Zweig. - Öhlschläger, Claudia (Lektüren der Ähnlichkeit um 1900.)

Maghemite nanoparticles synthesis via spray flame synthesis and particle characterization by hole in a tube sampling and scanning mobility particle sizing (HIAT-SMPS) (Applications in Energy and Combustion Science)
In order to standardize spray flame synthesis (SFS) studies, intensive work has been done in recent years on the design of burner types. Thus, in 2019, the so-called SpraySyn1 burner was introduced (SS1), which was subsequently characterized in numerical and experimental studies. Based on this research, a modification of the nozzle design was proposed, which has now been considered in the successor model, SpraySyn2 (SS2). As little is known about the effect of the nozzle adaptation on the particle formation, we operated both burners under identical operating conditions to produce maghemite. The final powder comparison showed that SS2 yielded considerable higher specific surface areas (associated with smaller primary particle sizes), lower polydispersity, and higher phase purity. To obtain further information on the size distributions of aggregates and agglomerates generated by SS2, aerosol samples were extracted by hole in a tube (HIAT) sampling and characterized by scanning mobility particle sizing (SMPS). Samples were extracted along the centerline at different heights above the burner (HAB) above the visible flame tip (>7 cm), and quenching experiments were performed to extract the aerosol samples at different dilution rates. Thereby, it was demonstrated that performing detailed quenching experiments is crucial for obtaining representative HIAT-SMPS data. In particular, agglomerates/aggregate sizes were overestimated by up to ~70 % if samples were not sufficiently diluted. If sufficient dilution was applied, distribution widths and mean particle mobility diameters were determined with high accuracy (sample standard derivation <5 %). Our data suggested the evolution of primary particle sizes was mostly completed <7 cm HAB and it was shown aggregates/agglomerates present above the visible flame were compact in structure (non- fractal). The mean diameter of the particle ensemble grew along the centerline from 6.9 nm (7 cm) to 11.4 nm (15 cm), while distribution widths grew from 1.42 to 1.52.
Keywords: Flame Spray Pyrolysis; SpraySyn2; Spray flame synthesis; Maghemite nanoparticles; Gas to particle-conversion; Hole in a tube sampling

Handbuch Poetikvorlesungen. Geschichte – Praktiken – Poetiken, hg. v. Gundela Hachmann, Julia Schöll u. Johanna Bohley, Berlin/Boston 2022 - Elit, Stefan (ZfdPh)

Mehrsprachigkeit in der Schule. Sprachbildung im und durch Sachunterricht.

Der Imperativ der Biographisierung und die Ambivalenzen individueller Verantwortungszuschreibung - Dahmen, Stephan (Responsibilisierung)

„4 THe BoYZ“ – Widmungen im Szene-Graffiti aus konstruktionsgrammatischer Perspektive. Die multimodale Relator-Konstruktion als grammatische Musterbildung im Horizont des Textes - Tophinke, Doris; Dübbert, Alexander (Konstruktionsgrammatik X. Textsorten und Textmuster als Konstruktionen?)

“A Short Introduction to the Film Glove and Touch Studies.” - Kraft, Kerstin

Post-configuration Activation of Hardware Trojans in FPGAs - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (Journal of Hardware and Systems Security)
Keywords: General Engineering; Energy Engineering and Power Technology

Professionalisierung für Sprachbildung aus Sicht von Sachunterrichtsstudierenden – Langzeitwirkungen eines Vertiefungsseminars in der ersten Phase der sachunterrichtsdidaktischen Lehrer* innenbildung. - Gövert, Andre; Niederhaus, Constanze; Blumberg, Eva (Mehrsprachigkeit in der Schule – Sprachbildung im und durch Sachunterricht)

DaZ-Kompetenzen angehender Lehrkräfte des Faches Sachunterricht sowie der aus dem Sachunterricht hervorgehenden Fächer - Vasylyeva, Tetyana; Ehmke, Timo; Gövert, Andre; Kassem, Amani; Niederhaus, Constanze (Mehrsprachigkeit in der Schule – Sprachbildung im und durch Sachunterricht)

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

ProDaZ Online-Tool Deutsch - Lammers, Ina; Büttner, Denise; Krechter, Romina

Pillar[5]arene-based dually crosslinked supramolecular gel as a sensor for the detection of adiponitrile - Rodin, Maksim; Helle, David; Kuckling, Dirk (Polymer Chemistry)
An SPR-based dually crosslinked gel sensor for adiponitrile bearing pillar[5]arene responsive sites with a low limit of detection was developed.
Keywords: Organic Chemistry; Polymers and Plastics; Biochemistry; Bioengineering

Preschoolers' Interactions with Social Robots: Investigating the Potential for Eliciting Metatalk and Critical Technological Thinking - Tolksdorf, Nils Frederik; Wildt, Eugenia; Rohlfing, Katharina (Companion of the 2024 ACM/IEEE International Conference on Human-Robot Interaction)

‚Schelmische‘ Post-DDR-Romane: Ingo Schulzes „Peter Holtz“ und Lea Streisands „Hufeland, Ecke Bötzow“ - Elit, Stefan (‚Topographisches‘ Schreiben: Lea Streisand, Paderborn, Wintersemester 2022/2023)

'Topographisches‘ Schreiben: Lea Streisand. Paderborn Wintersemester 2022/23

Klopstocks lyrisches Spätwerk. Perspektivwechsel und Blickerweiterungen - Elit, Stefan („Wer wird nicht einen Klopstock loben?“ Friedrich Gottlieb Klopstocks poetische Innovationen und ihre produktive Rezeption)

Métodos de la mediación de cultura en el entrenamiento práctico de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Revista Lengua y Cultura)
This study investigates the teaching methods that future teachers of German as a foreign language use in cultural mediation. Utilizing a qualitative and hermeneutic approach, it analyzes data from a teacher-training module of the International Master's in German as a Foreign/Second Language that Friedrich Schiller University Jena in Germany offers. Participants taught an online course to students from a Japanese university, which focused on cultural learning. Within the teacher training module, the participants discussed their lesson plans, conducted classes, and subsequently reflected on their teaching practices by exploring and critiquing the practical application of their teaching skills. The analysis, which was conducted using qualitative evaluative content analysis following Kuckartz's (2018) approach, revealed a preference for distributive/instructive methods, with some recognition of interactive and collaborative methods. A tendency towards both repetitive and reflective practices was evident, with a predominant focus on content that was specific to a supposed target culture rather than intercultural or transcultural content. The study highlights the need to balance knowledge transmission with the development of critical and reflective skills in cultural mediation. It emphasizes the importance of incorporating collaborative and interactive methods, which promote a critical attitude that is necessary in language teachers and learners. In conclusion, this study advocates adaptive and reflective teaching as an essential component in the training of future language teachers in globalized contexts.
Keywords: cultural mediation; teacher training; foreign language teaching; teaching methods; teaching practice

“Der Draht ist gut, hält uns ab vom dummen Leben“. Ironisierung als kommunikativer Versuch des Umgangs mit Entwertungs- und Gewalterfahrungen durch jüdische Textproduzenten im Getto Litzmannstadt - Markewitz, Friedrich (Invective Discourse)
Immediately after the National Socialist seizure of power, a comprehen-sive social, legal and ultimately existential exclusion of Jewish people began. The disturbing perception of the break-up of previous understandings of the world was intensified against the background of the acts of annihilation by the National Socialists. Countering this in a communicative form became an often agonizing challenge for Jewish speakers, but also a necessary need. This paper will focus on a communicative phenomenon that has been little researched in linguistics so far: The use of irony to counter experiences of devaluation and violence. By eval-uating ironic utterances in textual communications of the Litzmannstadt ghetto, the criticism of elements of National Socialist ideology will be tentatively made understandable, as well as the experiences of violence within the ghetto.

Haus oder Schule? oder Haus und Schule? Zur kulturell-gesellschaftlichen Bedeutung der historischen Textsorte 'Schulprogramm' hinsichtlich der Konstitution, Festigung wie Abgrenzung des Erziehungssystems im 19. Jahrhundert - Markewitz, Friedrich (Textsorten in Sprach-, Kultur- und Sozialgeschichte)

Ironie - Markewitz, Friedrich
Ironie lässt sich als uneigentliches Kommunikationsmittel beschreiben, mit dem etwas anderes zum Ausdruck gebracht wird, als Sprecher*innen oder Schreiber*innen eigentlich meinen. Dies erfordert eine Differenzierung in Gesagtes und Gemeintes. Doch diese Differenzierung ist längst nicht immer eindeutig und so lebt Ironie von einer interpretatorischen Ambivalenz, ob eine Äußerung wörtlich oder ironisch zu verstehen ist. Aufgrund dieser Ambivalenz und ihrer kulturgeschichtlichen Entwicklung erscheint Ironie als ebenso faszinierendes wie komplexes Sprach-Phänomen. Die vorliegende Einführung gibt aus kulturlinguistischer Perspektive Einblicke in die verschiedenen Möglichkeiten der theoretischen Beschreibung, methodischen Erfassung sowie empirischen Analyse von Ironie. Dabei werden einerseits alltagssprachliche Formen ironischen Kommunizierens in den Blick genommen, andererseits Möglichkeiten des interdisziplinären Anschlusses, um Ironie als linguistisches sowie als kulturgeschichtliches Phänomen zugänglich zu machen.

Gebete im Islamischen Religionsunterricht - Candan, Ayse Beyza (Zum Gebet einladen. Impulse aus der Praxis des evangelischen, islamischen und katholischen Religionsunterrichts.)

Forschungsstand zu Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland: ein Scoping Review - Noetzel, Ida; Becker, Linda; Gräfin v. Plettenberg, Elisabeth; Kehne, Miriam (Forum Kinder- und Jugendsport)
Die Studienlage zum Thema Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland zeigt sich vielseitig. Das Forschungsfeld ist neben wenigen umfassenden, überregionalen Studien durch kleinere Studien mit spezifischen inhaltlichen Schwerpunkten gekennzeichnet. Das vorliegende Scoping Review zielt darauf ab, die Erkenntnisse des Forschungsfeldes der circa vergangenen 20 Jahre zu systematisieren. Leitend ist die Forschungsfrage „Wie stellt sich der aktuelle Forschungsstand im Feld von Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland dar?“ Auf Basis einer systematischen Literaturrecherche in fünf Datenbanken konnten aus 2365 Publikationen 52 in die Analyse eingeschlossen werden. Überwiegend wurden regionale Querschnittsstudien mit spezifischem Fokus durchgeführt. Die Studien befassen sich zumeist mit den Rahmenbedingungen von Bewegung, Spiel und Sport im Ganztag sowie mit den Charakteristika von Bewegung, Spiel und Sport im Ganztag. Die Analyse verdeutlicht unter anderem den Mangel an längsschnittlichen Studien sowie den Forschungsbedarf im Bereich der Qualität von Bewegung in diesem Setting.
Keywords: Review; Ganztag; Bewegung; Spiel; Sport; Forschungsstand

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

“It’s like I got a new pair of glasses”: Reflections on sense of self, home, and belonging among transnational students in short-term study abroad programs - Müller, Mareike (Study Abroad Research in Second Language Acquisition and International Education)
This study focuses on a specific group of sojourners that has thus far remained rather unexplored in the context of study-abroad research, namely, students with extensive prior experiences of living in, traveling to, and/or familial ties with target-language mediated communities. To this end, this study examines data obtained through episodic interviews with three American students, who grew up in close contact with German-speaking communities and studied abroad in Austria for four weeks. By means of thematic analysis, the pre-study abroad sojourn motives and reflections on sense of self, home, and belonging are contrasted with these students’ immediate and delayed post-study abroad accounts. The results shed light on both the challenges young adults grapple with due to their international biographies and the transformative effects students attribute to their short-term sojourns with regard to redefining who they are and what meaning different places of home and heritage have within their individual trajectories.

Concepciones de cultura y de encuentros interculturales de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Memorias del III Congreso Internacional de Lenguas, Lingüística y Traducción)

Die Sporthalle – Ein Raum zum Sprachenlernen? Zwischen der Forderung nach Integration durch Sport und Sprache(n) als Schlüssel zur Integration - Treder, Alexandra (Transdisziplinäre Räume in den Kultrwissenschaften)

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Mit tiergestützter Pädagogik soziale Teilhabe fördern! - Mombeck, Mona Maria

Soziale Grenzen und Grenzbearbeitungen. Ein Zugang zur sozialwissenschaftlichen Bildungsforschung - Haker, Christoph; Otterspeer, Lukas (Bildungsforschung: Erziehungswissenschaftliche Perspektiven)
Der Beitrag führt in die von uns verfolgte Forschungsperspektive der sozialen Grenzen und Grenzbearbeitungen ein und bringt diese mit den Begriffen Bildung und Bildungsforschung zusammen. Unsere Theoretisierung beginnt mit einem sozialtheoretisch unterbestimmten Verständnis sozialer Grenzen und Grenzbearbeitungen. Dieses erhebt einerseits den Anspruch, nah an Alltagserfahrungen mit sozialen Grenzen und Grenzbearbeitungen zu sein. Andererseits ermöglicht es den Einstieg in ganz unterschiedliche Sozialtheorien und damit eine multiperspektivische Forschungspraxis. Dieses Potential plausibilisieren wir am Beispiel von Analysen zu Fragestellungen der Wissenschafts- und Rechtsextremismusforschung, die wir selbst durchgeführt haben. Für Bildung und Bildungsforschung sind in diesem Zusammenhang der Blick auf Bildungsprozesse, Bildungsinstitutionen und die Konzeption von Forschung als eine selbstreflexive Bildungspraxis relevant.

Tailored metrics for assessing the quality of MBSE models - Gräßler, Iris; Wiechel, Dominik; Özcan, Deniz; Taplick, Patrick (Proceedings of the Design Society)
Abstract System models are used to merge relevant engineering artefacts and relationships. Therefore, a high model quality must be ensured. Currently, there is no method for defining company-specific metrics to assess system model quality. In a six-step research approach, a method is defined: (1) literature analysis on quality assessment approaches, (2) derivation of success factors, (3) evaluation of approaches, (4) development of a method, (5) application in automotive industry, and (6) evaluation. The method supports system engineers to derive tailored metrics to objectively assess the model quality.

Antonia Villinger: Dramen der Schwangerschaft. Friedrich Hebbels „Judith“, „Maria Magdalena“ und „Genoveva“. Baden-Baden: Ergon 2021 - Famula, Marta (Jahrbuch Forum Vormärz Forschung 2022. [in Vorbereitung])

Literaturen vom 19. bis zum 21. Jahrhundert (thematische, ästhetische, mediale Transformationen hin zu einer technologisch aufgerüsteten Weltkommunikation) - Öhlschläger, Claudia (Grundthemen der Literaturwissenschaft: Weltliteratur.)

Rezension: Chiara Conterno / Astrid Dröse: Deutsch-italienischer Kulturtransfer im 18. Jahrhundert. Konstellationen, Medien, Kontexte - Süwolto, Leonie (DAJ)

Politisch-humanistische Positionen in Reisenarrativen über Frankreich der 1920er und 1930er Jahre:„La lumière“ – Joseph Roths poetischer und medienreflexiver Humanismus - Öhlschläger, Claudia (Narrative des Humanismus in der Weimarer Republik und im Exil. Zur Aktualität einer kulturpolitischen Herausforderung für Europa.)

Die Schrift entHeiligen. Praktisch-theologische Überlegungen zum Bibelgebrauch als Transformation des Heiligen - Schroeter-Wittke, Harald (Heilige Schriften in der Kritik. XVII. Europäischer Kongress für Theologie (5.-8. September 2021 in Zürich). VWGTh 68)

Distortional effects of separate accounting and formula apportionment on factor allocation - Ortmann, Regina; Pummerer, Erich (Journal of Business Economics)
Abstract We examine distortions caused by tax base allocation systems–separate accounting (SA) or formula apportionment (FA)–with respect to the allocation of assets and workforce within multinational entities (MNEs). The effects of both systems are intensively debated by EU Member States as they are striving to implement a European tax system. Its introduction would lead to a switch from SA to FA. Moreover, Pillar One of the recent global tax reform includes a mix of both tax base allocation systems. We find that, against the claims of the EU, FA does not necessarily create lower distortions of the factor allocation. Decisive for that assessment is the level of profit shifting under SA. Our results indicate that, in tendency, the factor allocation is more severely distorted by FA when the profit shifting possibilities were rather low under SA. In contrast to former studies, we highlight the importance of analyzing the status quo under the recently applied system (SA) in order to be able to assess the consequences of a switch from SA to FA. Our results are interesting for policy-makers as they help anticipating reactions of MNEs to a change in the applied tax base allocation system and for companies as a basis for future tax planning.
Keywords: Economics and Econometrics; Business and International Management

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology

Predicting the Bond Quality of Heavy Copper Wire Bonds using a Friction Model Approach - Althoff, Simon
Ultraschall-Drahtbonden ist eine Standardtechnologie im Bereich der Aufbau- und Verbindungstechnik von Leistungshalbleitermodulen. Um Prozessschritte und damit wertvolle Zeit zu sparen, sollen die Kupferdickdrähte für die Leistungshalbleiter auch für die Kontaktierung von eingespritzten Anschlusssteckern im Modulrahmen verwendet werden. Das Kontaktierungsverfahren mit diesen Drähten auf Steckern in dünnwandigen Kunststoffrahmen führt häufig zu unzureichender Bondqualität. In dieser Arbeit wird das Bonden von Anschlusssteckern experimentell und anhand von Simulationen untersucht, um die Prozessstabilität zu steigern. Zunächst wurden Experimente auf Untergründen mit hoher Steifigkeit durchgeführt, um Störgrößen von Untergrundeigenschaften zu verringern. Die gewonnenen Erkenntnisse erlaubten die Entwicklung eines Simulationsmodells für die Vorhersage der Bondqualität. Dieses basiert auf einer flächenaufgelösten Reibarbeitsbestimmung im Fügebereich unter Berücksichtigung des Ultraschallerweichungseffektes und der hierdurch entstehenden hohen Drahtverformung. Experimente an den Anschlusssteckern im Modulrahmen zeigten eine verringerte Relativverschiebung zwischen Draht und Stecker, was zu einer deutlichen Verringerung der Reibarbeit führt. Außerdem wurden verminderte Schwingamplituden des Bondwerkzeugs nachgewiesen. Dies führt zu einer weiteren Reduktion der Reibarbeit. Beide Effekte wurden mithilfe eines Mehrmassenschwingers modelliert. Die gewonnenen Erkenntnisse und die erstellten Simulationsmodelle ermöglichen die Entwicklung von Klemmvorrichtungen, welche die identifizierten Störgrößen gezielt kompensieren und so ein verlässliches Bonden der Anschlussstecker im gleichen Prozessschritt ermöglichen, in dem auch die Leistungshalbleiter kontaktiert werden.
Keywords: heavy copper bonding; wire bonding; quality prediction; friction model; point-contact-element

Sprachliche Bildung - Topalović, Elvira; Settinieri, Julia

A Unifying Approach to Efficient (Near-)Gathering of Disoriented Robots with Limited Visibility - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Proceedings of the 26th International Conference on Principles of Distributed Systems (OPODIS))

Beep-and-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Theor. Comput. Sci.)

Near-Term Effects of Short-Term Study Abroad: A Longitudinal Examination of Learner Perceptions - Müller, Mareike (Frontiers: The Interdisciplinary Journal of Study Abroad)
A relatively small body of research has been conducted on the near- and long-term effects of study abroad (SA) to date. This existing research suggests that SA effects on language skills tend to be volatile, while the impact on various aspects of learners’ personal, academic, and professional development may be longer-lasting. Yet, learner perspectives on the dynamics and durability of such effects, in particular in the context of short-term SA programs, remain largely unexplored. This study hence investigates the near-term impact of short-term SA programs as experienced by students within the first months and years following their sojourns. A qualitative case-study design is employed to examine the accounts of four American students of German, who studied abroad in Austria for four weeks and were interviewed repeatedly over a period of up to 40 months after their sojourns. The results suggest that, from the students’ perspective, many effects deteriorate in the near term, although the overall sojourn experience still appears influential. Abstract in German Nur wenige Forschungsvorhaben haben sich bislang den mittel- bis langfristigen Auswirkungen studentischer Auslandsaufenthalte gewidmet; die bisherige Datenlage deutet jedoch darauf hin, dass die Auswirkungen auf sprachliche Kompetenzen eher unbeständig sind, wohingegen die persönliche, studiums- und berufsbezogene Entwicklung der Lernenden länger von einem Auslandsaufenthalt beeinflusst wird. Die Dynamik und Beständigkeit derartiger Auswirkungen wurden jedoch kaum mit Blick auf kurze Auslandsaufenthalte (≤ acht Wochen) sowie aus der Perspektive der Studierenden erforscht, was die vorliegende Studie insbesondere hinsichtlich mittelfristiger Effekte fokussiert. Mittels eines qualitativen Fallstudiendesigns werden die Interviewdaten vier amerikanischer Deutschlernender untersucht, die sich vier Wochen in Österreich aufhielten und in einem Zeitraum von bis zu 40 Monaten nach ihrem Aufenthalt wiederholt befragt wurden. Die Ergebnisse zeigen, dass viele Auswirkungen eines solchen Aufenthalts aus studentischer Perspektive mittelfristig verblassen, auch wenn der Auslandsaufenthalt im Gesamten weiterhin als einflussreiche Erfahrung wahrgenommen wird.

Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert

Distribution Network Optimization: Predicting computation times to design scenario analysis for network operators - Burmeister, Sascha Christian; Schryen, Guido (Energy Systems)

Musiklandschaften zwischen Rhein und Weser – Einführung - Meine, Sabine; Otto, Arnold; Süßmann, Johannes (Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert)

Minimum Edge Cuts in Overlay Networks - Schweichhart, Jonas

"Lesungen vor Kindern sind für mich Theater" / Salah Naouras Sicht auf Wirkliches und Mögliches in Autor*innenlesungen für Kinder in der Schule - Kruse, Iris; Maubach, Bernd; Tönsing, Johanna (Salah Naoura)